2012
DOI: 10.1177/1352458512451943
|View full text |Cite
|
Sign up to set email alerts
|

Radiologically isolated syndrome – incidental magnetic resonance imaging findings suggestive of multiple sclerosis, a systematic review

Abstract: With increasing availability of magnetic resonance imaging (MRI), there is also an increase in incidental abnormal findings. MRI findings suggestive of multiple sclerosis in persons without typical multiple sclerosis symptoms and with normal neurological findings are defined as radiologically isolated syndrome (RIS). Half of the persons with RIS have their initial MRI because of headache, and some have a subclinical cognitive impairment similar to that seen in multiple sclerosis. Radiological measurements also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
103
0
12

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(116 citation statements)
references
References 36 publications
1
103
0
12
Order By: Relevance
“…None of the patients admitted in the RIS phase, which is included in our study were receiving a conventional MS treatment. Most common complaint among the RIS patients was identified to be headache in various studies as found in this study (1,5,10).…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…None of the patients admitted in the RIS phase, which is included in our study were receiving a conventional MS treatment. Most common complaint among the RIS patients was identified to be headache in various studies as found in this study (1,5,10).…”
Section: Resultsmentioning
confidence: 74%
“…Approximately in two-thirds of the patients develop radiographic progression within the first 5 years. When the number of lesions in the MRI is high (> 9), gadolinium (Gd) enhancement of the asymptomatic lesions is present and in particular if cervical cord lesions are seen, clinical conversion rate is higher (2,5,6,7,17,18,19). In our study, 8 of 49 patients had subsequent neurological episodes during the follow-up period, and thus began to be followed by a diagnosis of Clinically Isolated Syndrome (CIS) -MS accordingly.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…40 % of these patients develop neurological symptoms, and 10 % will formally meet the diagnostic criteria for multiple sclerosis [31]. Detected asymptomatic myelon lesions increases the risk of developing symptoms [32]. As a rule, patients who eventually develop a neurological deficit also exhibit a progression of lesions in T2w and FLAIR images.…”
Section: Radiological Isolated Syndromementioning
confidence: 99%
“…As a rule, patients who eventually develop a neurological deficit also exhibit a progression of lesions in T2w and FLAIR images. Although there is no current consensus regarding the type and extent of possible therapy [32], a neurological work-up should be performed (Category II).…”
Section: Radiological Isolated Syndromementioning
confidence: 99%